Noneffectiveness of scopolamine for facilitating detection of upper gastrointestinal neoplasia during screening esophagogastroduodenoscopy: propensity score-matched study - Omata, Fumio; Kumakura, Yasuhisa; Ishii, Naoki; Deshpande, Gautam A.; Matoba, Kohei; Ohmuro, Akemi; Rai, Fumie; Takashima, Misako; Kato, Akira; Masuda, Katsunori (Endoscopy, 2020)
Background Antispasmodics, such as scopolamine, are widely used in several countries prior to diagnostic and screening esophagogastroduodenoscopy (EGD), with the goal of optimizing the detection of minute lesions, typically early gastric cancer (T1 lesions). The aim of this study was to determine whether scopolamine facilitates detection of gastric cancer in the screening setting.Methods A propensity score-matched retrospective study was conducted in a tertiary referral medical center in Tokyo, Japan. Consecutive individuals (n = 40 776) underwent screening EGD between January 2011 and May 2016. All outcome lesions were diagnosed with histopathological confirmation. Detection of esophageal cancer, gastric adenoma, duodenal adenoma, and upper gastrointestinal neoplasia (UGIN) were investigated as secondary outcomes.Results Scopolamine was used in 31 130 patients (76.3 %) and propensity score matching yielded 6625 pairs. Bivariate analysis revealed no significant association between possible confounders (age, sex, overweight, atrophic gastritis, alcohol history, smoking history, midazolam use, endoscopist biopsy rate grade, and gastric cancer in first-degree relatives) and scopolamine use. Lesions detected were 18 gastric cancers, 11 esophageal cancers, 19 gastric adenomas, 6 duodenal adenomas, and 54 UGINs, with no significant association between scopolamine use and lesion detection.Conclusions Scopolamine use did not appear to effectively facilitate detection of gastric or esophageal cancer, gastric or duodenal adenoma, and UGIN during screening EGD. Scopolamine should be avoided until its efficacy is confirmed by a randomized controlled trial.